Ecotheology-based character education for primary students: A comparative analysis of Indonesia and Egypt - Aminulloh Aminulloh; Khairul Umam; Achmad Fauzan Adimah; Fahrur Rozi; Mohammad Mu'tashim Billah (EDUCARE Journal of Primary Education, 2026)
The current threats of environmental degradation and climate change increasingly require the integration of moral, spiritual, and ecological perspectives into primary school curricula, particularly in Muslim-majority contexts. This study aims to analyze how ecotheology-based character and values education can be constructed for primary school students through a comparative perspective between Indonesia and Egypt. The study employed an asymmetrical qualitative comparative case study design, combining Participatory Action Research (PAR) in Indonesia, document analysis in Egypt, observation, interviews, reflective journals, documentation, and cross-case thematic analysis to formulate an educational model. The findings revealed three key points. First, ecotheological principles were implemented through different pedagogical approaches: Indonesia integrated the values of khalifah, amanah, and ihsan through experiential learning, whereas Egypt embedded them implicitly through the curriculum and teacher mediation. Second, both models positioned teachers as key actors; Indonesia emphasized participatory-contextual practices, while Egypt was more oriented toward the formal curriculum in shaping ecological character. Third, the framework can be transferred to other Muslim countries by integrating Islamic theology, experiential learning, teacher mediation, reflection, and community involvement to internalize ecological character. This study concludes that Indonesia’s participatory experience and Egypt’s curriculum-based approach need to be integrated with Islamic theology, critical reflection, teacher roles, and community engagement to internalize students’ ecological character authentically and sustainably. The study recommends strengthening the ecotheology curriculum through teacher training, experiential learning, value reflection, and community partnerships so that students’ ecological character can be internalized and contextually adapted in other Muslim countries in a sustainable manner.